2005
DOI: 10.1111/j.1365-2672.2004.02496.x
|View full text |Cite
|
Sign up to set email alerts
|

The simultaneous detection of both enteroviruses and adenoviruses in environmental water samples including tap water with an integrated cell culture-multiplex-nested PCR procedure

Abstract: Aims:To evaluate an integrated cell culture (ICC)-multiplex-nested PCR using the buffalo green monkey kidney (BGMK) cells for the simultaneous detection of both enteroviruses and adenoviruses in surface water and tap water samples and optimize the procedure for more sensitive detection of virus showing no apparent cytopathic effect (CPE). Methods and Results: A total of 69 surface water and 50 tap water samples were analysed by the ICC-multiplexnested PCR. All the PCRs were performed five times with a cell lys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
43
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 45 publications
3
43
0
1
Order By: Relevance
“…The authors detected EV in 57% of surface water samples, while only 37% of samples were positive for AdV. Slightly higher EV detection was also related to Lee et al (2005), who detected EV in 33.3% of surface water samples collected from Han River (Seoul, Korea) and AdV in 30.4% of samples. Chapron et al (2000) verified a similar situation, with higher EV detection (58.6%) than AdV (48.3%) in surface water samples.…”
Section: Discussionmentioning
confidence: 98%
“…The authors detected EV in 57% of surface water samples, while only 37% of samples were positive for AdV. Slightly higher EV detection was also related to Lee et al (2005), who detected EV in 33.3% of surface water samples collected from Han River (Seoul, Korea) and AdV in 30.4% of samples. Chapron et al (2000) verified a similar situation, with higher EV detection (58.6%) than AdV (48.3%) in surface water samples.…”
Section: Discussionmentioning
confidence: 98%
“…However, PCR results may not reflect the infectivity of the samples since PCR only detects the genes of the pathogens; therefore, integrated cell culture-PCR (ICC-PCR) was developed to identify the specific infectious enteric viruses. ICC-PCR has been used to detect infectious enteric viruses in river water, tap water, beach water, and wastewater effluent samples (28,29,39,50). However, Buffalo green monkey (BGM) cell culture, currently recommended by the EPA, has been compared with other cell lines, such as A549 and PLC/PRC/5 (28,39), and the results showed that enteric viruses were propagated better with these cell lines than with BGM cells.…”
mentioning
confidence: 99%
“…Although HAdVs have frequently been identified in various environments such as wastewater (19,22,39,41), drinking waters (20,30,31,55), groundwater (28,40), surface waters (7,15,17,25,42,44), and pool recreational waters (35,38,50,54), quantitative information for HAdV occurrence at public lake beaches is still insufficient. The overall goal of this study was to gain insight into HAdV abundance in freshwaters at two popular recreational beaches on Lake Michigan using quantitative PCR assays.…”
mentioning
confidence: 99%